The Symbolic Meaning of Taboo Expressions in The Mourning Tradition of The Gorontalo Community and Their Relevance to Indonesian Language Learning - Fitrawati R. Usman; Dakia N. Djou; Asna Ntelu (Universitas Islam Negeri Palopo, 2026)
This study examines the forms and symbolic meanings of taboo expressions in the mourning tradition of the Gorontalo community and their relevance to Indonesian language learning. Academically, this study is important because mourning taboo expressions represent local cultural knowledge reflecting social values, belief systems, and symbolic communication practices that remain underexplored. The novelty of this study lies in applying Ferdinand de Saussure’s semiotic perspective to analyze mourning taboo expressions and connect their cultural meanings to educational contexts. This study employed a descriptive qualitative approach through fieldwork conducted in Tibawa District, Gorontalo Regency, involving 10 informants. Data were collected through interviews, observations, and documentation and analyzed through data reduction, data presentation, and conclusion drawing. The findings identified 15 taboo expressions classified into three categories: five direct taboo expressions, two indirect taboo expressions, and eight myth-based taboo expressions. Semiotic analysis revealed that these expressions function not only as social prohibitions but also as ideological and cultural instruments for transmitting local values across generations. The findings are relevant to local wisdom-based literacy and explanatory text materials in Indonesian language learning.